2020
DOI: 10.1101/2020.03.02.19007088
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic susceptibility for major depressive disorder associates with trajectories of depressive symptoms across childhood and adolescence

Abstract: Background: Depression that onsets during childhood and adolescence is associated with worse illness course and outcomes. However, the genetic factors that influence risk for early-onset depression remain mostly unknown. Using data collected over thirteen years, we examined whether polygenic risk scores (PRS) capturing genetic risk for major depressive disorder (MDD) were associated with early-onset depressive symptoms, as assessed from childhood to adolescence. Methods: Data came from the Avon Longitudinal St… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Major depressive disorder (MDD) is one of the most common, costly, and disabling mental disorders, with lifetime prevalence estimated at 11.7% among adolescents (Merikangas et al, 2010) and 16.6% among adults in the United States (Kessler et al, 2005). Whereas depression can emerge at any point in the life course, nearly one third of those who have depression report a first onset before age 21 (Zisook et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Major depressive disorder (MDD) is one of the most common, costly, and disabling mental disorders, with lifetime prevalence estimated at 11.7% among adolescents (Merikangas et al, 2010) and 16.6% among adults in the United States (Kessler et al, 2005). Whereas depression can emerge at any point in the life course, nearly one third of those who have depression report a first onset before age 21 (Zisook et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Extant work has indicated that depression PRS were associated with childhood-persistent depression and early-adult onset depression in a predominantly European-ancestry sample (Kwong et al, 2019). Other work has shown that a depression PRS was associated with increasing and high depressive symptoms across childhood and adolescence (Lussier et al, 2020) and a steep increase in depressive symptoms in adolescence and young adulthood (Kwong et al, 2020) in Europeanancestry samples. Additional research has indicated that in a European-ancestry sample, depression PRS were associated with late adolescent depression, but not low or early-onset adolescent depression (Rice et al, 2019).…”
Section: Introductionmentioning
confidence: 99%